Optimasi Line Balancing PCB Televisi LCD dengan Lean Manufacturing dan RPW - Solihin Solihin; Rifki Muhendra; Murwan Widyantoro; Al Munawir Al Munawir (universitas teuku umar, 2026)
The electronics manufacturing industry, particularly in Printed Circuit Board (PCB) assembly for LCD televisions, requires highly efficient production systems to meet output targets and improve labor productivity. One of the critical issues frequently encountered is assembly line imbalance, characterized by bottlenecks, idle time, and uneven workload distribution across workstations. This study aims to optimize line balancing in the PCB production line of LCD TV Model P14xx by integrating the Ranked Positional Weight (RPW) method with a Lean Manufacturing approach. The research begins with an initial condition analysis to evaluate line efficiency, balance delay, and bottleneck locations. Subsequently, Lean Manufacturing tools are applied to identify and eliminate non-value-added activities (waste) within the production process. The RPW method is then implemented to optimize task allocation based on positional weights while considering precedence constraints. The results demonstrate that the integrated approach significantly improves production system performance. Line efficiency increases from 69% to 82%, while balance delay decreases from 31% to 18%. Additionally, the number of workstations is reduced from 15 to 10, and labor productivity improves from 10.5 to 15.4 units per operator.